81 Suitability of cardiac resynchronisation therapy in patients with univentricular and systemic right ventricular hearts. (5th June 2017) - Demetriades, Polyvios; Bell, Alexandra; Christopher, Gubran; Clift, Paul; Thorne, Sara; Bowater, Sarah; Marshall, Howard; DeBono, Joseph; Hudsmith, Lucy
Abstract : Introduction: Cardiac resynchronisation therapy (CRT) is a well-recognised treatment in patients with systolic heart failure complicated by ventricular dyssychrony. However, there is limited evidence to support its use in patients with congenital heart disease and particularly those with univentricular hearts or systemic right ventricles (RV). In 2014, the PACES/HRS published a consensus statement recommending CRT in these populations. The indications in patients with univentricular hearts include ventricular EF of 35%, with QRS duration 150 ms in a LBBB or RBBB morphology (spontaneous or paced), ventricular dilatation and NYHA II-IV symptoms. In contrast, in patients with systemic RV, CRT is recommended if ejection fraction is <35% with RV dilatation, NYHA II-IV, RBBB, QRS duration >150 ms in non-paced and NYHA I-IV and >40% V-pacing in paced. Methods: We performed a retrospective analysis for EF, QRS duration and NYHA status, from 203 patients with a Fontan circulation (univentricular) and 55 patients with congenitally corrected Transposition of the Great Arteries (ccTGA, systemic RV) under specialist Adult Congenital Heart disease (ACHD) follow-up to assess the suitability for CRT according to the guidelines. Results: Table 1 shows data collected from both groups of patients. Univentricular functional data from the Fontan population was available for 194 patients. Only 5% had EF 35%. QRS duration was available for 190 patients and was 150ms in 3% and 47% of patients were NYHA II-IV. Ejection fraction data was available for 54 ccTGA patients and was 35% in 11%. QRS duration was 150ms in 26% and 31% were NYHA II-IV. In total, only two patients with Fontan circulation and only one from the ccTGA population qualified for CRT according to the current recommendations. One patient had CRT implanted in 2010 and is well to follow-up in NYHA II. Discussion: We have assessed the suitability of CRT recommendations in a large pool of univentricular and systemic RV patients. We have identified very few candidates for CRT within this cohort. Unfortunately, there is little evidence to support CRT in ACHD setting. Furthermore, procedural and technical difficulties, potential complications including infection and associated morbidity and mortality, ventricular morphology, co-existent cardiac pathologies, the aetiology of ventricular dyssynchrony and cardiomyopathic disease per se also require specific consideration before CRT is recommended. Decision to implant CRT in univentricular ACHD patients is more complex than guidelines suggest and requires discussion in a combined ACHD electrophysiology multidisciplinary meeting involving the patient at all levels.